Dual antiplatelet pre-treatment with aspirin and ticagrelor in ACS patients undergoing unplanned aortocoronary bypass surgery - Salbach, Christian; Yildirim, Mustafa; Gulba, Rebecca; Milles, Barbara Ruth; Biener, Moritz; Müller-Hennessen, Matthias; Hund, Hauke; Frey, Norbert; Giannitsis, Evangelos (Clinical research in cardiology, 2025)
Major bleedings following coronary artery bypass grafting (CABG) have significant implications on outcomes in acute coronary syndrome (ACS) patients. Owing fears of fatal bleedings in case of urgent CABG, current guidelines recommend a cessation of P2Y12 receptor antagonists (P2Y12-RA) before cardiac surgery and opt against routine pre-treatment with a P2Y12-RA before coronary angiography (CA). However, sparse information exists outside randomized trials on the frequency of urgent CABG and the consequences of inappropriately long cessation of P2Y12-RA treatment in patients presenting with ACS.